PENENTUAN DISPATCHING RULES PADA PENJADWALAN DUA MESIN CNC YANG DISUSUN SECARA SERIES - Sembiring, Ezra Mahyani; Irwan, Hery; Tarigan, Petra Paulus (University of Riau Kepulauan, 2023)
PT. KOP is a company engaged in oil and gas drilling. This company has 4 products, where the company uses 2 machines arranged in parallel. The product is finished on 2 machines with two setups. PT. KOP often experiences delivery delays due to inaccurate production scheduling. This study applies the scheduling of proposals using the SPT (Shortest Processing Time), LPT (Longest Processing Time), and Jhonson methods. The results of this study indicate that the Johnson method is a better method than the SPT (Shortest Processing Time) and LPT (Longest Processing Time). Johnson's method has the minimum delay time. In the first week, the delay was 1 hour, 16 hours in the second week, 48 hours in the third week, and 86 hours in the fourth week. From the results of the flow time data using the Johnson method, namely 1 hour in the first week, 16 hours in the second week, 48 hours in the third week, and 86 hours in the fourth week. There is a savings in tooling usage of 50%. Series machines only require 4 tooling, while parallel machines require 8 tooling.